Nurses’ health and work experiences during the COVID-19 pandemic in Swedish prehospital and hospital care: a deductive content analysis through the lens of the swAge model - Cicilia Nagel; Petra Nilsson Lindstrom; Albert Westergren; Sophie Schon Persson; Kerstin Nilsson (BMC Public Health)
Abstract Working as a nurse offers job security but also poses risks for mental health issues. This study aims to explore factors and processes that affected health and work experiences among nurses in Sweden during the COVID-19 pandemic. Semi-structured interviews were conducted with 14 nurses from high COVID-19 patient load areas (ambulance, emergency departments, ICU, infection wards, and specialized COVID-19 wards). A deductive content analysis using the SwAge model’s nine determinant areas, was performed. The COREQ-checklist was adhered to. Nurses were prepared to sacrifice their health for the well-being of their patients, with many still facing the repercussions. They voiced their disappointment with healthcare organizations for providing insufficient support. The pandemic disrupted the social contract between healthcare organizations and the public, particularly in elder care. To perform effectively, nurses need adequate staffing, a safe work environment, fair compensation, manageable workloads, and recognition. Instances of deception and broken promises have undermined trust and professional well-being. During the pandemic, nurses leaned on their colleagues for support to manage stress and compensate for shortcomings. Nonetheless, nurses also reported experiencing resilience, adaptability, and flourishing. Nurses in Sweden face challenges such as undersized organizations and the need for primary care expansion to reduce hospital burdens. A better balance of resources is essential for effective performance. Improved working conditions and organizational support are crucial for retaining nurses. Identifying factors for a sustainable working life involves understanding key areas and their interactions. Healthcare organizations and managers should consider these areas to promote sustainability.